PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP LOYALITAS PELANGGAN PADA PT TIGA SERANGKAI SURAKARTA - Bangkit Tyas Sada Wardiyanti; Putut Haribowo; Rif'ah Dwi Astuti (Politeknik Negeri Semarang, 2019)
This research aims to determine the effect of the components of Customer Relationship Management (CRM) which consists of people, process, and technology on customer loyalty at PT Tiga Serangkai Pustaka Mandiri General Book (GB) Division Central Java-DIY Branch. Data collection methods in this research by interview, observation, and questionnaires to 51 respondents using purposive sampling technique. Methods of data analysis used are validity test, reliability test, classic assumption test, multiple linear regression test, t test, F test, and coefficient of determination. The results of this research shows that the variables of people, process, and technology have positive and significant effect both simultaneously or partially on the customer loyalty variable model of multiple linear regression analysis results as follows Customer Loyalty = 3,781 + 0,289 People + 0,320 Process + 0,247 Technology. The results of the analysis obtained Adjusted R2 value of 0.685, this shows that the contribution of independent variables in influencing the dependent variable is 68.5% and the remainder is influenced by other variables not examined in this research.